2008
DOI: 10.1097/dad.0b013e31816de820
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Distinction of Cutaneous Spindle Cell Carcinoma

Abstract: Cutaneous spindle cell squamous carcinoma is an uncommon variant of squamous cell carcinoma in which keratinocytes infiltrate the dermis as single cells with elongated nuclei rather than as cohesive nests or islands, and signs of keratinization of conventional squamous cell carcinoma are insubstantial or nonexistent. Spindle cell carcinoma must be distinguished from spindle cell/desmoplastic melanoma, cutaneous leiomyosarcoma, atypical fibroxanthoma (AFX), and scar. In instances when there is no definitive evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 15 publications
1
77
5
Order By: Relevance
“…QPCR analysis, which displays increased sensitivity for detecting low expression levels of isoforms, dem onstrated infrequent expression of TP63 isoforms in primary human melanocyte cultures but significantly elevated expres sion in >70% of established melanoma cell lines. In contrast with previous immunohistochemistry studies, which showed little or no expression of p63 protein (Brinck et al, 2002;Di Como et al, 2002;ReisFilho et al, 2003b;Dotto and Glusac, 2006;Bourne et al, 2008;Morgan et al, 2008;Sakiz et al, 2009;Kanner et al, 2010), our data provide the first evi dence of marked upregulation of both p63 mRNA and pro tein in melanoma cell lines.…”
Section: Depletion Of P63 Sensitizes Melanoma Cells To a Mitochondriacontrasting
confidence: 54%
See 1 more Smart Citation
“…QPCR analysis, which displays increased sensitivity for detecting low expression levels of isoforms, dem onstrated infrequent expression of TP63 isoforms in primary human melanocyte cultures but significantly elevated expres sion in >70% of established melanoma cell lines. In contrast with previous immunohistochemistry studies, which showed little or no expression of p63 protein (Brinck et al, 2002;Di Como et al, 2002;ReisFilho et al, 2003b;Dotto and Glusac, 2006;Bourne et al, 2008;Morgan et al, 2008;Sakiz et al, 2009;Kanner et al, 2010), our data provide the first evi dence of marked upregulation of both p63 mRNA and pro tein in melanoma cell lines.…”
Section: Depletion Of P63 Sensitizes Melanoma Cells To a Mitochondriacontrasting
confidence: 54%
“…Expression of TAp63 and Np63 in uveal melanoma was dem onstrated in 12/18 (66.7%) and 1/18 (5.6%) cell lines, respec tively (Kilic et al, 2008). Other studies have suggested a lack of p63 expression in melanoma in situ or invasive disease Dotto and Glusac, 2006;Bourne et al, 2008;Morgan et al, 2008;Sakiz et al, 2009;Glusac, 2011).…”
mentioning
confidence: 93%
“…37 Whether CD68 can become important in terms of classification remains to be determined. Currently, the reason for the ectopic CD68 expression remains unclear 20,38,39 and we interpret this histiocytic feature of desmoplastic melanoma as part of the Abbreviations: c þ n, cytoplasmic and nuclear staining were combined; N, number of cases. P-value derived from Fisher's exact test.…”
Section: There Is a Dearth Of Specific Desmoplastic Melanoma Markersmentioning
confidence: 99%
“…The present tumor is carcinoma. Atypical fibroxanthoma and desmoplastic melanoma was excluded because the present tumor expressed various CKs and did not express HMB45, Melan-A, SOX10, MITF; [3][4][5][6][7][8][9][10] the specificity of S100 protein is low, [3][4][5][6][7][8][9][10] the possibility of desmoplastic melanoma is quite unlikely. Because the present tumor expressed CKs, it is carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] These two variants of skin SCC lack keratinization and intercellular bridge, thus causing diagnostic problems. [1][2][3][4][5][6][7][8][9][10] The author herein reports a case of desmoplastic SCC composed predominantly of spindle cells.…”
Section: Introductionmentioning
confidence: 99%